Analysis of the Influence of Product Completeness, Service and Price on Consumer Repeat Purchase Decisions - Andy Yusuf Susanto; J.E. Sutanto (Publikasi Indonesia, 2023)
This study aims to determine the effect of product completeness, service, and price on consumer purchasing decisions at Sumber Sehat Departemen Store, Singaraja - Bali. The variables studied were product completeness (X1), service (X2), price (X3) and customer purchasing decision (Y). Product completeness variable has 4 (four) indicators, which are the diversity of products sold, the variety of products sold, the availability of products sold, and the availability of various brands. Service variable have 5 (five) indicators, which are physical facilities, reliability, certainty, responsiveness, empathy. Price variable has 3 (three) indicators, which are price affordability, price competitiveness and price benefits suitablility. Purchasing decision variable has 5 (five) indicators, which are product preference, brand preference, store preference, time preference and quantity preference. The analytical tool used is multiple linear regression with the help of SPSS software. The population in this study is the total consumers of Sumber Sehat Convenience Store in 2021, namely as many as 531 consumers and the sampling method used is Slovin formula with a tolerated margin of error of 5%, so that a sample of 228 respondents is obtained. The results of this study indicate that the variable product completeness, service and price have a positive and significant effect on the consumer purchasing decision variable. Furthermore, the variables of product completeness, services and prices simultaneously have a positive and significant effect on the consumer purchasing decision variable.